RADI-19. The Incidence of New Brain Metastases in Patients with Non-Small Cell Lung Cancer Following Discontinuation of Systemic Therapy. (9th August 2021) - London, Dennis; Patel, Dev; Donahue, Bernadine; Navarro, Ralph; Gurewitz, Jason; Silverman, Joshua; Sulman, Erik; Bernstein, Kenneth; Palermo, Amy; Golfinos, John; Sabari, Joshua; Shum, Elaine; et al.
Abstract: Purpose: Patients with non-small cell lung cancer (NSCLC) metastatic to the brain increasingly are living longer due to improvements in systemic therapy and local modalities. The risk of new brain metastases when these patients stop systemic therapy is unknown. Recognizing patterns of new tumor occurrence is necessary to determine the frequency of follow-up and the need for further treatment. Methods: We included patients in a prospective registry who had non-small cell lung cancer (NSCLC) brain metastases, discontinued systemic therapy for at least 90 days, and underwent active surveillance. 63 patients with 73 off-periods were studied. The risk factors for the development of new tumors were determined using Cox regression and multi-state Markov modeling. Results: The median time to new brain metastases off systemic therapy was 16.0 months. The probability of developing an additional new tumor at 6, 12, and 18 months was 26%, 40%, and 53%, respectively. There were no additional new tumors 22 months after stopping therapy. Patients who discontinued therapy due to intolerance or progression of the disease and those with mutations in RAS or receptor tyrosine kinase pathways (e.g. KRAS, EGFR) were more likely to develop new tumors (HR: 2.21, 95% CI: 1.25–3.91, p=6.3 x 10 –3 ; HR: 2.03, 95% CI: 1.09–3.77, p=0.026, respectively). Conclusion: The rate of new brain metastases from NSCLC in patients off systemic therapy decreases over time and is uncommon 2 years after cessation of cancer therapy. Patients who stop therapy due to toxicity or who have RAS or receptor tyrosine kinase pathway mutations have a higher rate of new metastases and should be followed more closely.